Study to Evaluate the Safety, Efficacy, and Duration of Dual Antiplatelet Therapy in Coronary Artery Disease Patients - Mary Dodda, Aashritha; Oggu Archana; Shiksha Netam; Bommagani Pavan Kumar; Emani Sai Sri Jayanthi (Journal of Cardiology and Cardiovascular Medicine, 2025)
Coronary artery disease (CAD) is a leading cause of mortality globally, characterized by the formation of atherosclerotic plaques that impede blood flow to the myocardium. Dual antiplatelet therapy (DAPT), combining aspirin with a P2Y12 inhibitor, is essential for reducing ischemic events post-coronary stenting. This paper aimed to evaluate the safety, efficacy, and optimal duration of DAPT with ECOSPRIN+TICAGRELOR versus ECOSPRIN+CLOPIDOGREL in CAD patients.